A survey of South Carolina pharmacists' readiness to prescribe human immunodeficiency virus pre‐exposure prophylaxis. Issue 4 (13th March 2023) - Burns, Charles M.; Endres, Kyle; Derrick, Caroline; Cooper, Alexandra; Fabel, Patricia; Okeke, Nwora Lance; Ahuja, Divya; Corneli, Amy; McKellar, Mehri S.
Abstract: Introduction: Human immunodeficiency virus (HIV) pre‐exposure prophylaxis (PrEP) is largely underutilized in the Southern United States. Given their community presence, pharmacists are well positioned to provide PrEP within rural, Southern regions. However, pharmacists' readiness to prescribe PrEP in these communities remains unknown. Objective: To determine the perceived feasibility and acceptability of prescribing PrEP by pharmacists in South Carolina (SC). Methods: We distributed a 43‐question online descriptive survey through the University of South Carolina Kennedy Pharmacy Innovation Center's listserv of licensed SC pharmacists. We assessed pharmacists' comfort, knowledge, and readiness to provide PrEP. Results: A total of 150 pharmacists responded to the survey. The majority were White (73%, n = 110), female (62%, n = 93), and non‐Hispanic (83%, n = 125). Pharmacists practiced in retail (25%, n = 37), hospital (22%, n = 33), independent (17%, n = 25), community (13%, n = 19), specialty (6%, n = 9), and academic settings (3%, n = 4); 11% ( n = 17) practiced in rural locales. Pharmacists viewed PrEP as both effective (97%, n = 122/125) and beneficial (74% n = 97/131) for their clients. Many pharmacists reported being ready (60% n = 79/130) and willing (86% n = 111/129) to prescribe PrEP, although over half (62% n = 73/118) cited lack of PrEP knowledge as a barrier. Pharmacists described pharmacies as an appropriate location to prescribe PrEP (72% n = 97/134). Conclusions: Most SC pharmacists surveyed considered PrEP to be effective and beneficial for individuals who frequent their pharmacy and are willing to prescribe this therapy if statewide statutes allow. Many felt that pharmacies are an appropriate location to prescribe PrEP but lack a complete understanding of required protocols to manage these patients. Further investigation into facilitators and barriers of pharmacy‐driven PrEP is needed to enhance utilization within communities.